Prescribing Antibiotics in Rural China: The Influence of Capital on Clinical Realities - Chen, Meixuan; Kadetz, Paul; Cabral, Christie; Lambert, Helen (Frontiers in Sociology, 2020)
Primary care clinicians in rural China are required to balance their immediate duty of care to their patients with patient expectations for antibiotics, financial pressures, and their wider responsibilities to public health. The clinicians in our sample appear to make greater efforts in managing immediate clinical risks and personal reputation than in considering the long-term consequences of their actions as potentially contributing to antimicrobial resistance. This paper employs Bourdieu's theory of capital to examine the perspectives and practices of Chinese primary care clinicians prescribing antibiotics at low-level health facilities in rural Anhui province, China. We examine the institutional context and clinical realities of these rural health facilities and identify how these influence the way clinicians utilize antibiotics in the management of common upper respiratory tract infections. Confronted with various official regulations and institutional pressures to generate revenues, informants' desire to maintain good relations with patients coupled with their concerns for patient safety result in tensions between their professional knowledge of “rational” antibiotic use and their actual prescribing practices. Informants often deferred responsibility for antimicrobial stewardship to the government or upper echelons of the healthcare system and drew on the powerful public discourse of “suzhi” (human quality) to legitimize their liberal prescribing of antibiotics in an imagined socioeconomic hierarchy. The demands of both practitioners' and patients' social, cultural, and economic forms of capital help to explain patterns of antibiotic prescribing in rural Chinese health facilities.